Three-dimensional reproducibility assessment of radiochromic ClearView™ gel in custom vessel. Issue 1 (1st January 2022) - Jordan, Kevin; Xu, Lu; Barnett, Rob
Abstract: Samples of the radiochromic hydrogel ClearView™ were characterized for 3D dosimeter performance in custom vessels and read with a modified Vista16 optical cone beam scanner as part of a small field dosimetry study. Uniform dose responses and small field depth doses revealed each sample was unique. As the gels aged over several weeks at 4 °C, the dose sensitivity decreased. Reconstructions of uniform dose distributions revealed unique features near the vessel interface. The central sub-volumes ranged from uniformity to within 2% throughout the sub-volume to a 12% gradient from base to top of gel. Comparisons of small field depth doses revealed that if the central volume had a uniform dose response, no correction was required. However, if a gradient in sensitivity from bottom to top was measured a correction may or may not be required. It is suspected that the filling protocol of the custom vessels is a factor in the observed variations in 3D dose response.